Comparison of Feeding Ability between Ischiodon scutellaris (Diptera: Syrphidae) and Menochilus sexmaculatus (Coleoptera: Coccinellidae) on Aphis craccivora (Hemiptera: Aphididae) - Adhyatma Noor Rizal; Nugroho Susetya Putra; Suputa Suputa (Jurnal Perlindungan Tanaman Indonesia, 2018)
Study on the feeding ability of two predators of Aphis craccivora (Koch), i.e. larvae of syrphid fly, Ischiodon scutellaris and coccinellid beetle, Menochilus sexmaculatus has been done in the laboratory. The study was conducted to determine the impacts of prey densities on larval development time, and the survival rate of larval stage. The results showed that M. sexmaculatus larvae required more prey than I. scutellaris in the 1st instar, but I. scutellaris ate more prey than M. sexmaculatus in the 3rd  instar. Furthermore, addition of prey number shortened significanly the development time of the larvae stage, almost all of 1st and 3rd instars M. sexmaculatus and I. scutellaris were able to develop into pupae, whereas, only 45% out of total 1st instar provided with 20 prey individuals succeed to pupate. The impact of the number of prey on the biology of aphidophaga in relation to their role as controlling aphid in nature is discussed in this paper. IntisariKajian tentang kemampuan makan dua predator Aphis craccivora (Koch), yaitu larva lalat syrphid, Ischiodon scutellaris dan kumbang koksi, Menochilus sexmaculatus telah dilakukan di laboratorium. Kajian juga dilakukan untuk memahami dampak jumlah mangsa pada lama perkembangan larva menjadi pupa dan keloloshidupan larva menjadi pupa. Hasil kajian menunjukkan bahwa larva M. sexmaculatus membutuhkan lebih banyak mangsa daripada I. scutellaris pada instar 1, namun I. scutellaris makan lebih banyak mangsa daripada M. sexmaculatus pada instar 3. Hasil penelitian juga menunjukkan bahwa penambahan mangsa mempercepat waktu perkembangan larva secara signifikan. Semua larva instar 1 dan 3 M. sexmaculatus dan I. scutellaris mampu lolos menjadi pupa, kecuali larva instar 1 M. sexmaculatus yang hanya mampu lolos menjadi pupa sebanyak 45% jika diberi mangsa 20 ekor. Dampak jumlah mangsa pada biologi afidofaga dalam kaitannya dengan peran mereka sebagai pengendali populasi kutu afid di alam dibahas dalam tulisan ini.